A Sandwich Method Using Kapandji Intrafocal Pinning to Facilitate Palmar Plating of Displaced Distal Radius Fractures. Issue 3 (September 2017) - Huang, Hui-Kuang; Huang, Yi-Chao; Wang, Jung-Pan; Chang, Ming-Chau
Abstract : The use of palmar plating in the treatment of dorsally displaced distal radius fracture is very common, and can result in a good functional outcome. We present an easy "sandwich method" to reduce the fracture and to facilitate osteosynthesis. Firstly, the dorsal Kapandji intrafocal wire was applied to achieve the reduction of the dorsally displaced fracture and provide a volar-directed force. Then the intra-articular fractures were reduced or the metaphyseal defect is stuffed with bone graft if necessary. Finally, the anatomical plate is used to buttress and push back the distal fragment to complete the osteosynthesis. The postoperative radiographic parameters, comparing with the contralateral noninjured side, could achieve similar radial height, radial inclination, volar tilt, and ulnar variance without significant difference.